2020
DOI: 10.9734/cjast/2020/v39i530549
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Induction Spray-charging System (Embedded Electrode) for Knapsack Mist-blower

Abstract: The introduction of electrically charged sprays in agricultural application has become inevitable for better control on droplet transference with reduced drift with less spray chemical requirements. The study was under taken to develop an electrostatic induction spray charging system as attachment to knapsack mist-blower. A high voltage generator was fabricated on the basis of Cockcroft-Walton voltage multiplier principle with input of 6 V DC battery. A self-atomizing hydraulic nozzle was developed to deliver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…This generates paths based on a virtual environment and on probabilistic road maps; these paths are then optimized with the NSGA-III algorithm. Dipak S. Khatawkar et al [17] designed an electrostatic-induction spray-charging device for backpack sprayers and found that the charge-to-mass ratio was highest at 5 kV voltage, 5 mm away from the atomization zone. Zhang Yueshun [18] designed an inter-row sprayer for solar greenhouses, which includes an additional working mode for spray bar lifting and spray bar fixation, producing inter-row spray and ordinary spray, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This generates paths based on a virtual environment and on probabilistic road maps; these paths are then optimized with the NSGA-III algorithm. Dipak S. Khatawkar et al [17] designed an electrostatic-induction spray-charging device for backpack sprayers and found that the charge-to-mass ratio was highest at 5 kV voltage, 5 mm away from the atomization zone. Zhang Yueshun [18] designed an inter-row sprayer for solar greenhouses, which includes an additional working mode for spray bar lifting and spray bar fixation, producing inter-row spray and ordinary spray, respectively.…”
Section: Introductionmentioning
confidence: 99%